Os demônios e o invisível - Charro, Alexandre Antonio (2024)
This work investigates traces of the removal of the Invisible in Western metaphysics and its consequences. Drawing on the research of Argentine philosopher Fabian Ludueña Romandini and his treatise on spectrality, we delve into the invisible realm of the spectrum and some of its other manifestations, such as daemons. The consequences of this distancing can be observed through the concept of algorithmic governmentality, developed by Belgian researchers Antoinette Rouvroy and Thomas Berns. The Amerindian cosmologies described by Yanomami Davi Kopenawa, Viveiros de Castro's anthropological perspective, and cinema are summoned to challenge the field and broaden the spectrum of the theme of the Invisible